The Accuracy of "Berkat Sayang" Aid in Poverty Alleviation In Sidoarjo District - Nabilah, Shafa Rizqi; Sarmini, Sarmini; Jacky, M; Harianto, Sugeng; Suprijono, Agus (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
The " Berkat Sayang" program is specifically for the elderly under the auspices of the Sidoarjo Regency Social Service. This article aims to analyze the accuracy of food assistance in reducing poverty in Sidoarjo using qualitative research methods and a descriptive approach. The results of the research explain that the “Berkat Sayang” program in Sidoarjo which is distributed to the elderly and people with disabilities is useful for reducing poverty rates has not been running properly. It requires (1) systematic and massive socialization regarding the " Berkat Sayang" program to recipients who meet the criteria of the Social Service (2) understanding of the benefits of the " Berkat Sayang" program by recipients is still relatively low so most are confused about why they received this assistance (3) quality food in the " Berkat Sayang" program needs to be evaluated by the Social Service (4) The distribution of the "Berkat Sayang”" program needs to be evaluated by the Social Service because it is not in accordance with planning